2013
DOI: 10.1002/anie.201302840
|View full text |Cite
|
Sign up to set email alerts
|

Selectively N‐Methylated Soluble IAPP Mimics as Potent IAPP Receptor Agonists and Nanomolar Inhibitors of Cytotoxic Self‐Assembly of Both IAPP and Aβ40

Abstract: The selective incorporation of N‐methyl groups in the highly amyloidogenic and cytotoxic sequence of the type 2 diabetes islet amyloid polypeptide (IAPP) generates a unique class of soluble and nontoxic IAPP mimics. These polypeptides combine potent IAPP receptor agonism with nanomolar‐affinity inhibitory potential on the amyloid formation and cell‐damaging effects of both IAPP and the Alzheimer's β‐amyloid peptide (Aβ40).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 38 publications
8
69
0
11
Order By: Relevance
“…Additionally, amylin likely improves glucose metabolism in the brain since it readily crosses the BBB [21], relaxes cerebrovascular structures thereby increasing blood supply to the brain [4, 5], and is shown to enhance neural regeneration [6]. Several studies have shown that monomeric amylin and its analogs inhibit the formation of Aβ aggregation, a key element in the AD pathogenesis [2226]. These results taken together could account for its positive association with cognition in elderly adults in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, amylin likely improves glucose metabolism in the brain since it readily crosses the BBB [21], relaxes cerebrovascular structures thereby increasing blood supply to the brain [4, 5], and is shown to enhance neural regeneration [6]. Several studies have shown that monomeric amylin and its analogs inhibit the formation of Aβ aggregation, a key element in the AD pathogenesis [2226]. These results taken together could account for its positive association with cognition in elderly adults in this study.…”
Section: Discussionmentioning
confidence: 99%
“…N-methyl peptides N-methylation of an SRE has one side able to bind to the target by hydrogen bonding (H-bond), while the other has an N-methyl in place of backbone H, thus preventing Hbonds. Selectively N-methylated soluble IAPP (islet amyloid polypeptide peptide) mimics nanomolar inhibitors of cytotoxic self-assembly of both IAPP and Ab1-40 [10].…”
Section: Retro-inverso (Ri) Peptidesmentioning
confidence: 99%
“…Conversely, A␤ binds prefibrillar IAPP, and A␤ and IAPP aggregates reciprocally regulate each other's cytotoxicity (50). IAPP inhibits the cytotoxicity of A␤ aggregates at nanomolar concentrations and inhibits A␤ fibrillation at stoichiometric ratios (51). Several small A␤ fragments bind to full-length IAPP, some with nanomolar affinity (52).…”
Section: Iappmentioning
confidence: 99%